Single-port endoscopic mastectomy via the lateral chest approach for the treatment of grade II gynecomastia. Issue 22 (29th May 2020) - Jian, Chenxing; Wu, Limin; Lin, Lisheng; Liu, Wei; Zheng, Zifang; Yang, Chunkang
Abstract : Abstract: To investigate the feasibility of single-port endoscopic mastectomy via the lateral chest approach in the treatment of Simon grade II gynecomastia. Data from 12 patients with grade II gynecomastia admitted from January 2017 to November 2018 were retrospectively analyzed, and related satisfaction surveys were conducted 6 months after the operation. All surgeries were successfully performed under single-port endoscopy, and no patients were converted to open surgery. There were no serious complications related to the surgery, and all the patients were satisfied with the postoperative appearance. The application of single-port endoscopy in the surgical treatment of grade II gynecomastia is safe and reliable.